Clinical and anamnestic features of pregnant women that have subchorionic hematomas - Natalia B. Kuznetsova; Irina O. Bushtyreva; Ekaterina A. Zabanova; Maria P. Dmitrieva; Angelina V. Bespalaya (Медицинский вестник Юга России, 2017)
Objective: researching of the clinical and anamnestic features of pregnant women have a 1-trimester abortion threat with the formation of a subchorionic hematoma (SCH), living in the Rostov region, and fi nd clinical and anamnestic risk factors of subchorionic hematoma. Materials and methods: in a study performed in State budgetary institution of the Rostov region Perinatal Center in years 2013-2016, 270 pregnant women with subchorionic hematoma in the period of 6-12 weeks of pregnancy and 79 pregnant women without subchorionic hematoma (relatively healthy) were included. Results: according to the study, the clinical and anamnestic features of the subchorionic hematoma in the Rostov region are lower body weight and body mass index, and the presence of uterine fi broids. Th e risk of subchorionic hematoma increases 19 times if woman has non-developing pregnancy history,8.5 times — reccurent miscarriage, 7.5 times — perinatal losses. Conclusion: history of early pregnancy losses, both single (one spontaneous abortion or one non-developing pregnancy) and two or more early reproductive losses, history of perinatal loss increase the risk of subchorionic hematoma in a case of pregnancy.